Sleep Duration and Quality as Modifiable Risk Factors for Type 2 Diabetes among Urban Young Adults - Fenita Purnama Sari; Besse Hardianti; Omry Pakpahan; Nur Aini Fatimah (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2026)
Sleep disorders are an emerging public health concern in large urban areas, where night-time activities, excessive gadget use, and psychosocial stress may contribute to increased metabolic disease risk, including type 2 diabetes mellitus (T2DM). While global studies have reported associations between sleep disturbances and T2DM, evidence among young urban adults in Indonesia remains limited. This cross-sectional study aimed to analyze the relationship between sleep duration and sleep quality with T2DM risk among 97 young adults aged 20–35 years living in South Jakarta, selected using [sampling method]. Sleep patterns were assessed using the Pittsburgh Sleep Quality Index (PSQI) and a sleep duration questionnaire, while T2DM risk was evaluated through fasting blood glucose and body mass index (BMI) measurements. Data were analyzed using logistic regression with a significance level of p<0.05. Results showed that 41.2% of respondents had poor sleep quality and 29.9% slept <6 hours per night. Individuals with sleep duration <6 hours had a 2.32-fold higher risk of T2DM (OR = 2.32; 95% CI: 1.10–4.21; p = 0.02) compared with those sleeping 7–8 hours. Respondents with poor sleep quality also had a significantly higher T2DM risk (OR = 1.98; 95% CI: 1.06–3.70; p = 0.01) and elevated fasting blood glucose levels. Additionally, participants with BMI ≥25 kg/m² had a 3.15-fold higher risk of T2DM (OR = 3.15; 95% CI: 1.47–6.42; p = 0.004). Short sleep duration, poor sleep quality, and overweight status are associated with an increased risk of T2DM among young urban adults in Jakarta. These findings highlight the importance of sleep hygiene education and weight management as early preventive strategies against diabetes in productive-age urban populations.